Comparison of the efficiency of anti-VEGF drugs intravitreal injections treatment with or without retinal laser photocoagulation for macular edema secondary to retinal vein occlusion: A systematic review and meta-analysis - Weijie Zou; Yuanyuan Du; Xiaoyan Ji; Ji Zhang; Hongping Ding; Jingqiao Chen; Tao Wang; Fangfang Ji; Jiang Huang; Jiang Huang (Frontiers Media S.A., 2022)
Objective: To compare the efficiency of anti-VEGF drugs intravitreal injections(IVI) treatment with or without retinal laser photocoagulation(LPC) for macular edema(ME) secondary to retinal vein occlusion(RVO).Methods: The randomized controlled trials and retrospective studies including anti-VEGF drug IVI combined with retinal LPC and single IVI in the treatment of macular edema secondary to RVO were collected in PubMed, Medline, Embase, Cochrane Library, and Web of Science. We extracted the main outcome indicators including the best corrected visual acuity (BCVA), central macular thickness(CMT), the number of injections and the progress of retinal non-perfusion areas(NPAs) for systematic evaluation, to observe whether IVI + LPC could be more effective on the prognosis of RVO. We use Review Manager 5.4 statistical software to analyze the dataResults: 527 articles were initially retrieved. We included 20 studies, with a total of 1387 patients who were divided into the combination(IVI + LPC) treatment group and the single IVI group. All the patients completed the ocular examination including BCVA, slit-lamp test, fundus examination and Optical Coherence Tomography(OCT) test before and after each treatment. There was no statistical difference between the combination treatment group and single IVI group on BCVA(WMD = 0.12,95%CI = -3.54-3.78,p = 0.95),CMT(WMD = -4.40,95%CI = -21.33-12.53,p = 0.61) and NPAs(WMD = 0.01,95%CI = -0.28-0.30,p = 0.94).However, the number of IVI was decreased significantly in the combination treatment group in BRVO patients, compared to that in the single IVI group(WMD = -0.69,95%CI = -1.18∼-0.21,p = 0.005).Conclusion: In the treatment of RVO patients with macular edema, the combination of IVI and retinal LPC neither improves BCVA nor reduces CMT significantly compared with the single IVI treatment. However, the combination treatment can decrease the number of intravitreal injections in patients with BRVO, while it is not observed in CRVO patients.